Smart E-Tickets: buying authentic and trustworthy tickets with blockchain - Santos, Daniel Filipe Martiniano dos (2019)
Tese de mestrado, Engenharia Informática (Engenharia de Software) Universidade de Lisboa, Faculdade de Ciências, 2019